The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3945/ajcn.116.134981
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia, hypercalciuria, and kidney stones in long-term studies of vitamin D supplementation: a systematic review and meta-analysis

Abstract: Long-term vitamin D supplementation resulted in increased risks of hypercalcemia and hypercalciuria, which were not dose related. However, vitamin D supplementation did not increase risk of kidney stones. Additional large RCTs of long-term vitamin D supplementation are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 72 publications
6
83
1
1
Order By: Relevance
“…When combined with calcium supplements, high-dose vitamin D results in a higher incidence of hypercalcemia and hypercalciuria than calcium supplements alone. (37) Unfortunately, we did not routinely measure 24-hour urine calcium in this study. Because black Americans conserve urine calcium more efficiently, it would be expected that they would be less likely than white Americans to develop hypercalciuria.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When combined with calcium supplements, high-dose vitamin D results in a higher incidence of hypercalcemia and hypercalciuria than calcium supplements alone. (37) Unfortunately, we did not routinely measure 24-hour urine calcium in this study. Because black Americans conserve urine calcium more efficiently, it would be expected that they would be less likely than white Americans to develop hypercalciuria.…”
Section: Discussionmentioning
confidence: 97%
“…When combined with calcium supplements, high‐dose vitamin D results in a higher incidence of hypercalcemia and hypercalciuria than calcium supplements alone . Unfortunately, we did not routinely measure 24‐hour urine calcium in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The recommended dose of vitamin D supplementation is 2000 IU per day or more depending on blood level. For those with a history of kidney stones, however, excess vitamin D intake should be avoided (Malihi et al 2016).…”
Section: Pay Attention To Physical Healthmentioning
confidence: 99%
“…Vitamin D receptor gene polymorphisms may influence vitamin D function, as well as its serum levels. In addition to the above, supplementation of vitamin D in humans and rats can induce hypercalciuria, renal calcification, and/or renal stones [55,56]. …”
Section: Discussionmentioning
confidence: 99%
“…However, many doctors and patients are concerned about whether vitamin D repletion will increase the risk of urolithiasis, especially in SFs [64]. A recent systematic review and meta-analysis demonstrated that long-term vitamin D supplementation resulted in increased risks of hypercalcemia and hypercalciuria, but did not increase risk of kidney stones [55]. A randomized controlled trial conducted in 21 SFs found that high-dose and low-dose vitamin D supplementation had no effect on urine calcium excretion or the supersaturation of calcium salts [65].…”
Section: Discussionmentioning
confidence: 99%